Lecture Duty Submission System In National University: Lecture Duty Submission System In National University - Sahrul Rasyid; Ucuk Darusalam; Sari Ningsi (Institute of Computer Science (IOCS), 2020)
The inefficient process of requesting lecturer workload at national universities tends to be ineffective because it still uses a manual system that makes lecturers feel slow. Due to the large number of other lecturer workload files that accumulate, making operators or HR forget to process when there are lecturers who submit workload sheets. The purpose of designing this system will produce a web-based lecturer workload program so that it makes it easy for lecturers to submit and process lecturer workload sheets. This software system development method uses the Waterfall Model. The results of making this application lecturers can easily make a report of the workload that is directly connected with the people concerned with the report of the workload itself so that the use of paper in making the report of the workload becomes reduced even almost not using the slightest paper.